Toward the technology of large cranberry fruit storage through declining the fungal rots - Andrianova, Tetiana; Konovalchuk, Valeriy (Problems of Environmental Biotechnology, 2021)
Study of fungal invasions and storage rots of cultivated large cranberry on experimental plots of commercial plantations in Rivno and Volyn’ oblasts during 2019–2020 are presented. Berries of the cultivar Wilcox, as more commercially promising, were selected for the final step of investigations. Losses of harvest were recorded during berries storage as a result of the pathogenic fungi infections and on the final step of study the plant material received post-harvest treatment by cold and hot water in different variants, with subsequent drying by warm air. There were examined storage results of the fruits collected in autumn and in early winter, percentage of different types of fungal rots development were estimated.